IN VITRO OVICIDAL AND LARVICIDAL ACTIVITY OF PSIDIUM CATTLEIANUM SABINE LEAVES AGAINST GASTROINTESTINAL NEMATODES OF SHEEP - Piza, M. L. S. T. [UNESP]; Feboli, A. [UNESP]; Augusto, J. G. [UNESP]; Anjos, L. A. [UNESP]; Laurentiz, A. C. [UNESP]; Royo, V. A.; Alvarenga, F. Q.; Laurentiz, R. S. [UNESP] (Inst Zootecnia, 2019)
Gastrointestinal nematodes can affect sheep productivity via severe weight loss, anemia and death. Infection control is generally performed with synthetic anthelmintic compounds; however, indiscriminate use of these drugs can stimulate the emergence of resistant nematodes. Thus, alternatives to the use of synthetic anthelmintic compounds have been proposed, such as the inclusion of medicinal plants in animal feed. The objective of this study was evaluate the anthelmintic activity of the leaves of the medicinal plant Psidium cattleianum Sabine (Araca) through its hydroalcoholic extract, and using in vitro assays with the eggs and larvae of gastrointestinal nematodes obtained from naturally infected donor sheep. The extract exhibited good in vitro ovicidal and larvicidal activity, with IC50 values of 0.55 mg mL(-1) for egg hatching inhibition, 0.20 mg mL-1 for larval development inhibition and an efficiency greater than 80% in the inhibition of larval migration at all concentrations evaluated (IC50 < 0.19 mg/mL). Phytochemical analysis detected higher concentrations of saponins, flavonoids, cardiac glycosides, anthraquinones and tannins in the extract. Our results demonstrated that the Psidium cattleianum Sabine's leaves exhibit in vitro anthelmintic activity, which suggests that in addition to its other medicinal properties, this plant can help control gastrointestinal nematodes in sheep. Future in vivo assays should be performed to confirm antiparasitic efficacy.
Keywords: Araca; Phytotherapy; Haemonchus contortus